Modelling Open Access Catalog (OPAC) Success using DeLone and McLean models in Library Agriculture Polytechnic of Samarinda - Dani Wahyudi Wahyudi; Suswanto; Reza Andrea (Politeknik Pertanian Negeri Samarinda, 2022)
Online Public Access Catalog (OPAC) is one of the systems used and utilized by the Samarinda State Agricultural Polytechnic library to provide information regarding the availability and collection of books owned by the library. The purpose of this study was to determine the success in implementing OPAC using the Delone and McLean Model. Consists of seven variables, namely information quality, system quality, service quality, usage, user convenience, interest in using, and net benefits. The data obtained from this study were obtained from the distribution of questionnaires using Google Forms and in writing, the research sample was obtained by 40 respondents. The results obtained in this study are in the form of conditions for each variable in the Delone and McLean Model. The user satisfaction and net benefit variables are in the high category, while the information quality and system quality variables are in the fairly high category. From the results obtained, it is necessary to prioritize improvements to the indicators owned by the Delone and McLean Model variables with the average percentage of each indicator which is below the average percentage of all indicators.